The Effect of Anti-Tumor Necrosis Factor-Alpha Treatment on Muscle Performance and Endurance in Patients With Ankylosing Spondylitis: A Prospective Follow-Up Study - Musa DEMİRKAPI and Mustafa Turgut YILDIZGÖREN and Hayal GÜLER and Ayşe Dicle TURHANOĞLU (Archives of Rheumatology, 2017)
Objectives: This study aims to evaluate muscle performance by using isokinetic dynamometer before and at third month of anti-tumor necrosis factor-alpha treatment in ankylosing spondylitis patients. Patients and methods: Thirty ankylosing spondylitis patients (23 males, 7 females; mean age 39.3±8.6 years; range 18 to 45 years) starting on anti- tumor necrosis factor-alpha treatment and 30 healthy controls (23 males, 7 females; mean age 39.1±8.8 years; range 18 to 48 years) with similar age, body mass index, and sex were enrolled. The clinical anthropometric measurements of chest expansion, lumbar Schober test, hand-finger floor distance and visual analog scale-global, C-reactive protein, erythrocyte sedimentation rate, Ankylosing Spondylitis Disease Activity Score-C-reactive protein and Ankylosing Spondylitis Disease Activity Score-erythrocyte sedimentation rate, Bath Ankylosing Spondylitis Disease Activity Index, Bath Ankylosing Spondylitis Metrology Index, Bath Ankylosing Spondylitis Disease Activity Index, Bath Ankylosing Spondylitis Metrology Index were determined before and at third month of the treatment. Results: There was no statistically significant difference in age, sex and, body mass index between the groups (p>0.05). A statistically significant difference was detected between 60 ̊/second and 180 ̊/second peak torque in angular velocity of flexor and extensor muscles (p<0.05). A significant difference was detected in respect to total work of patients with 180 ̊/second peak torque in angular velocity of flexor and extensor muscles (p<0.05). There was a statistically significant difference between the findings of 60 ̊/second and 180 ̊/second peak torque in angular velocity of flexor and extensor muscles (p<0.05). Isokinetic test results were better at third month after treatment than before treatment. Conclusion: The results of this study showed that both functional limitations and performance and endurance of muscles may be improved with anti-tumor necrosis factor-alpha treatment in ankylosing spondylitis patients.